Visual Outcome in Open Globe Injury - Rajkarnikar, Sagar; Bist, Ramesh Raj; Gurung, Anu; Shrestha, Ram (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Ocular trauma is a major cause of monocular blindness and visual impairment throughout the world. It is estimated that more than 2 million people suffer from ocular trauma annually and 40,000 become visually handicapped permanently. The aim of this study was to evaluate the visual outcome in open globe injury patients. Methods: This study was conducted in Nepal Eye Hospital. All the cases of admitted open globe injuries were examined and managed in the hospital were included in this study. The detail history of trauma and visual acuity was recorded. Clinical diagnosis was made after detail examination of anterior and posterior segment. Patient was treated according to the type of injury. Visual recovery and the cause of poor vision at the time of discharge was also noted. Data was analyzed using the SPSS 11 program. Results: Out of the 100 cases enrolled in the study work related injury was the most frequent injury, metal was the most common causative agent. Males of 20-50 years of age are more vulnerable to open globe injury. Vision improved in 48%, same vision in 39% and deteriorated vision in 13% cases was recorded. Conclusions: Present study reveals that open globe injury can present in varying severity and though the overall prognosis is grave, prompt surgical intervention can result in better visual outcome. The visual outcome in mild to moderate ocular injury was satisfactory but poor in severe injuries. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/40-43 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7909